Microscopic mechanism study of the creep properties of soil based on the energy scale method - Yuan, Jie; Wang, Tao Jin; Chen, Jian; Huang, jian An (Frontiers in Materials, 2023)
The study of the creep properties of soils is of great importance for the management of future settlements and the safe use of buildings. However, starting from the micro level is an effective way to explore the creep mechanism of soft soil. In this paper, the influence of the mineral composition and the mineral content on the structure and creep properties of soft soil was analyzed at the microscopic level and the energy scale method was proposed. Then, the energy scale method was used to analyze and discuss the results of the direct shear creep test. The discussion showed that 1) the average viscosity coefficient of kaolin was greater than that of bentonite, which decreased with an increase of kaolin and bentonite; 2) the thickness of adsorbed water or the double electric layer (DEL) on the particle surface was positively correlated with the soft soil creep; and 3) λ was positively correlated with the adsorbed water content and negatively correlated with the average viscosity coefficient of the soft soil. λ characterized the adsorption capacity of the particles at the micro level; hence, the energy scale method can explain the mechanism of the soft soil creep at the microscopic level and also quantitatively describe the influencing law of the basic characteristics of the particles on the properties of the soft soil creep.